2016
DOI: 10.1017/ice.2016.153
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Carbapenemase-Producing Carbapenem-Resistant Enterobacteriaceae (CP-CRE) Acquisition Among Contacts of Newly Diagnosed CP-CRE Patients

Abstract: objective. Carbapenemase-producing carbapenem-resistant Enterobacteriaceae (CP-CRE) are extremely drug-resistant pathogens. Screening of contacts of newly identified CP-CRE patients is an important step to limit further transmission. We aimed to determine the risk factors for CP-CRE acquisition among patients exposed to a CP-CRE index patient.methods. A matched case-control study was performed in a tertiary care hospital in Israel. The study population was comprised of patients who underwent rectal screening f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
(63 reference statements)
8
27
1
2
Order By: Relevance
“…We observed several outbreaks during the study period and the source of transmission was not always identified: contact with an index patient for 3 days is an independent risk factor for CP Enterobacteriaceae acquisition among contacts (Schwartz-Neiderman et al, 2016). In all cases a late acquisition of CPKP during hospitalization was demonstrated.…”
Section: Discussionmentioning
confidence: 86%
“…We observed several outbreaks during the study period and the source of transmission was not always identified: contact with an index patient for 3 days is an independent risk factor for CP Enterobacteriaceae acquisition among contacts (Schwartz-Neiderman et al, 2016). In all cases a late acquisition of CPKP during hospitalization was demonstrated.…”
Section: Discussionmentioning
confidence: 86%
“…Glycopeptide use was also identified to be a risk factor for carbapenem-resistant P. aeruginosa (15,17) and ESBL-producing bacteria (18) acquisition. On the contrary, 4 out of 13 significant risk factors were also described to be protective against CRE acquisition by other authors: quinolone use (19), mechanical ventilation (20), cephalosporin use (21), and ICU admission (22). Kwak et al speculated that fluoroquinolone use was found to be a protective factor because this antibiotic was often given as a substitute for carbapenem or cephalosporin antibiotics (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences in the mortality rates were observed based on the duration of treatment. Previous studies have reported various risk factors associated with CRE infections and patient deaths, such as antibiotic exposure, ICU stay, poor functional status, septic shock, dialysis, age >60 years, ventilation, presence of another multidrug-resistant organism, duration of contact, presence of central venous catheters, and receipt of immunosuppressive drugs (20,21). Logistic regression model performed in this study revealed the significant predictors were septic shock, Charlson index two and renal impairment.…”
Section: Page 7607mentioning
confidence: 56%